AB0754 Kawanet: The french registry for kawasaki disease (KD). (23rd January 2014) - Piram, M.; Koné-paut, I.; Djemoui, A.; Dallochio, A.; Lechevalier, P.; Gajdos, V.; Launay, E.; Eyssette-Guerreau, S.; Ballot, C.; Michelet, I.; Poignant, S.; Leblanc, A.; et al.
Abstract : Background: KD is the main vasculitis affecting children ≤5 years and the leading cause of acquired ischemic cardiopathy at adult age.While increasing in developing countries, thanks to robust epidemiologic surveys, the incidence of KD is only few reported in Europe and unknown in France. Objectives: The registry is aimed to assess the epidemiological characteristics of KD, to describe complete clinical features and responses to treatment.The registry is a tool for future cohort studies and supports international genetic studies(GWAS) aimed to characterized genetic factors associated to disease pathogenesis and complications. Methods: All institutional physicians susceptible to deal with a patient with KD were informed of a national registry since June 2011 through emails, phone calls, dedicated brochure, and scientific societies information and meetings. Patients to include were those suspected with KD and seen since January 2011. An eCRF has been built and implemented in a web secured database(CLEANWeb).The collection of data is planned to last ≥3 years. Results: Enrolments have started in may 2011.111 cases have been reported to the registry and complete information is available for 51 in January 2012, enrolled by 22 physicians from 18 centres. They were 25 males and 26 females: 29 European Caucasians, 7 Eastern Caucasians or North Africans, 11 afro-Caribbean's, 1 Asian and 3 of mixed ancestry. All but 1 were born in France.The median age at diagnosis was 2, 3y(2m-14y). The clinical symptoms were fever≥5 days (n=46), conjunctivitis(76%), cheilitis(87%), oral erythema(60%), cervical adenopathy(36%), diffuse exanthema(77%), perineal erythema(30%), changes over extremities(67%). Associated symptoms were abdominal(n=32), cardio-vascular(n=20), respiratory(n=17), neurological(n=13). Cardiac complications were reported in 16/45 patients(35%): 10 coronary dilatations, 4 coronary aneurysms, 8 pericarditis, 3 myocarditis. Age <1 year at onset was associated with cardiac complications. At diagnosis, 19 patients had complete KD according to the AAC definition and 32 patients were incomplete.46 patients received intravenous immunoglobulins (data unknown in 5 patients):29 patients responded to 1 course, 14 required 2 courses, 7 required steroids, 42 received Aspirin and 1 Anti-TNF. The mean delay between fever onset and treatment was 6.6 d(median 5 d). Follow-up visit is available for 36 patients. Conclusions: We described herein the first series of KD in France.Although our registry is not yet exhaustive, an important effort is made to inform the countrywide physicians concerned by KD to include children and adults seen for this disease.With a prospective inclusion of all patients with KD, we would be able to describe the epidemiology of the disease in France, the prognostic criteria in this population and to participate to the international consortium studying genetic factors associated to the disease.A prospective follow-up of these patients will informed us about the evolution of the disease in adulthood and the morbidity associated to the disease. Disclosure of Interest: None Declared